2012
DOI: 10.1186/1748-717x-7-139
|View full text |Cite
|
Sign up to set email alerts
|

Seminal vesicle interfraction displacement and margins in image guided radiotherapy for prostate cancer

Abstract: BackgroundTo analyze interfraction motion of seminal vesicles (SV), and its motion relative to rectal and bladder filling.Methods and MaterialsSV and prostate were contoured on 771 daily computed tomography “on rails” scans from 24 prostate cancer patients undergoing radiotherapy. Random and systematic errors for SV centroid displacement were measured relative to the prostate centroid. Margins required for complete geometric coverage of SV were determined using isotropic expansion of reference contours. SV mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 19 publications
0
41
0
Order By: Relevance
“…Four of 22 patients (18%) in the study had a reduction in target EUD from 5.6% to 14.4% compared with the preplanned EUD, which should not be acceptable clinically. Interfraction target (prostate and SV) deformation/rotation and intrafraction target motion were the major causes of the target dose reduction (26,27). Figure 2 shows the treatment dose deficits of the 4 patients who had large target EUD reductions (>5%) in the Daily Correction treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Four of 22 patients (18%) in the study had a reduction in target EUD from 5.6% to 14.4% compared with the preplanned EUD, which should not be acceptable clinically. Interfraction target (prostate and SV) deformation/rotation and intrafraction target motion were the major causes of the target dose reduction (26,27). Figure 2 shows the treatment dose deficits of the 4 patients who had large target EUD reductions (>5%) in the Daily Correction treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Dosimetric studies evaluating delivered dose after soft‐tissue CBCT‐based image guidance have found that the prostate and PSV will typically receive the planned V95% . However, PSV inclusion within the PTV is more likely to be negatively impacted by large bladder and rectal volume differences than the prostate . ROs and RTs who completed the prostate IGRT survey indicated that both the CBCT prostate and PSV volumes must be within the PTV after online soft‐tissue matching in order to proceed with treatment delivery (C. Hargrave, T. Deegan, M Poulsen, T. Bednarz, F. Harden and K. Mengersen, unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…34,35 However, PSV inclusion within the PTV is more likely to be negatively impacted by large bladder and rectal volume differences than the prostate. 36 ROs and RTs who completed the prostate IGRT survey indicated that both the CBCT prostate and PSV volumes must be within the PTV after online soft-tissue matching in order to proceed with treatment delivery (C. Hargrave, T. Deegan, M Poulsen, T. Bednarz, F. Harden and K. Mengersen, unpublished results). Therefore, BN performance, where the prostate and PSV metrics most influenced the decision to treat, and rectum and PSV metrics most influenced the probability of TPC, is as expected given the results of the prostate IGRT survey and the evidence in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has several limitations. We considered the prostate only and did not include seminal vesicles which are more prone to movement . We only captured the prostate location at the end of treatment, not the full intrafraction excursion of the prostate.…”
Section: Discussionmentioning
confidence: 99%
“…We considered the prostate only and did not include seminal vesicles which are more prone to movement. 25 We only captured the prostate location at the end of treatment, not the full intrafraction excursion of the prostate. As noted by Hatton et al, 14 the impact on dose delivered to the prostate could be considered 'worst case' as all motions of the prostate were not considered.…”
Section: Discussionmentioning
confidence: 99%